Enoxaparin for thromboprophylaxis in hospitalized COVID‐19 patients: The X‐COVID‐19 Randomized Trial. (26th December 2021) - Morici, Nuccia; Podda, GianMarco; Birocchi, Simone; Bonacchini, Luca; Merli, Marco; Trezzi, Michele; Massaini, Gianluca; Agostinis, Marco; Carioti, Giulia; Saverio Serino, Francesco; Gazzaniga, Gianluca; Barberis, Daniela; et al.
Abstract: Background: It is uncertain whether higher doses of anticoagulants than recommended for thromboprophylaxis are necessary in COVID‐19 patients hospitalized in general wards Methods: This is a multicentre, open‐label, randomized trial performed in 9 Italian centres, comparing 40 mg b.i.d. versus 40 mg o.d. enoxaparin in COVID‐19 patients, between April 30 2020 and April 25 2021. Primary efficacy outcome was in‐hospital incidence of venous thromboembolism (VTE): asymptomatic or symptomatic proximal deep vein thrombosis (DVT) diagnosed by serial compression ultrasonography (CUS), and/or symptomatic pulmonary embolism (PE) diagnosed by computed tomography angiography (CTA). Secondary endpoints included each individual component of the primary efficacy outcome and a composite of death, VTE, mechanical ventilation, stroke, myocardial infarction, admission to ICU. Safety outcomes included major bleeding. Results: The study was interrupted prematurely due to slow recruitment. We included 183 (96%) of the 189 enrolled patients in the primary analysis (91 in b.i.d., 92 in o.d.). Primary efficacy outcome occurred in 6 patients (6.5%, 0 DVT, 6 PE) in the o.d. group and 0 in the b.id. group (ARR 6.5, 95% CI: 1.5–11.6). The absence of concomitant DVT and imaging characteristics suggests that most pulmonary artery occlusions were actually caused by local thrombi rather than PE. Statistically nonsignificant differences in secondary and safety endpoints were observed, with two major bleeding events in each arm. Conclusions: No DVT developed in COVID‐19 patients hospitalized in general wards, independently of enoxaparin dosing used for thromboprophylaxis. Pulmonary artery occlusions developed only in the o.d. group. Our trial is underpowered and with few events.